Transformation plasticity and kinetic during bainite transformation on a 22MnB5 steel grade: Umwandlungsplastizität und ‐kinetik während der bainitischen Umwandlung des Stahls 22MnB5. Issue 8 (21st July 2016) - Schicchi, D. S.; Hunkel, M.
Abstract : The use of press hardening components has widely increased in the last decades in the automotive industry due to the possibility to obtain high strength parts with ductile zones for energy absorption. Conventional and partial press hardening are used depending on the needed properties of the final components. Quenching, and thus phase transformation, are performed within the tool under an applied load, making plausible to assume for the transformation plasticity effect to play a main role, leading to a minimized spring‐back effect. The influence of stresses, especially larger than austenite yield strength (high stresses), and pre‐strain on the bainite transformation kinetics are discussed for a 22MnB5 steel grade. Experimental evidence of the strong nonlinearity of the transformation plasticity of bainite regarding the applied stresses and differences between tensile and compression cases are here introduced.